Infancy in 21st Century Hungary: A Project Introduction: Policy, Theoretical and Methodological Framework and Objectives of the First National Representative Parent Survey on Infant and Early Childhood Mental Health - Danis, Ildikó; Bóné, Veronika; Hegedűs, Réka; Pilinszki, Attila; Szabó, Tünde; Dávid, Beáta (European Journal of Mental Health, 2020)
Objectives: Infancy in 21st Century Hungary is the first Hungarian national representative parent survey to examine early childhood mental health problems and important individual, family and broader environmental risk and protective factors associated with them. Methods: In the study, families raising children aged 3–36 months were included. The sample was nationally representative according to the children’s age and gender, and the type of residence. Data were collected in the winter of 2019–2020 from 980 mothers and 122 fathers. The parents were interviewed using a CAPI (computer-assisted personal interview) instrument at first, and then they filled out a self-administered questionnaire (SAQ). The measurement package was planned by an interdisciplinary research network coordinated by the Institute of Mental Health at Semmelweis University, while the sampling and the data collection were conducted by the TÁRKI Research Institute. Results: Based on the parental reports, we will examine the prevalence of infant and early childhood mental health problems perceived by the parents, and the relationships between the background variables measured in several ecological levels. Due to the representative sample’s socio-demographic diversity, we can map the generalizable variability of each examined construct and identify risk and protective factors behind the perceived developmental and mental health difficulties. Conclusions: In this article, the policy, theoretical and methodological framework, the justification and objectives of the research, and the measurement package are presented.